Shock tube evaluation on C2H4 ignition delay differences among N2, Ar, He, CO2 diluent gases. Issue 4 (August 2020) - Xiong, Xiaohe; Lv, Zhaomin; Tan, Houzhang; Peng, Zhimin; Ding, Yanjun
Abstract: To reveal the fuel ignition delay differences among diluent gases, non-reactive gas Ar, He, N2 and reactive gas CO2 four gases were selected to compare the ethylene ignition delay difference on a shock tube rig. The tested condition temperature and pressure range is 1074–1832 K and 2 atm. Comparison results show that the ethylene ignition delay discrepancy was not pronounced among Ar, He and N2 these non-reactive dilution gases. In terms of CO2 dilution, a critical CO2 concentration was observed. When the CO2 concentration was lower than this critical value, no distinguished ignition delay difference was found. Conversely, the ignition delay difference was pronounced once the CO2 concentration was above this critical value. Particularly, the difference was specially apparent in low temperature conditions. Reaction dynamic analysis shows that the heat effect is predominant in low temperature while the chemical effect is predominant in high temperature in the reaction of CO2 participation. Additionally, the CH* and OH* radical emission signal intensity turns smaller and profile curve turns irregular as the CO2 ratio increases. The CO2 shows a strong inhibition effect which is closely related with H radical consumption reaction CO2 +HCO + OH. Highlights: Ignition delay time in N2, Ar, He, CO2 four types of diluent gases were well investigated. As high as 94.92% CO2 dilution ratio was studied and a critical value CO2 was found. The strong inhibition effect on free radical of CO2 dilution was observed. The thermal effect, third body effect and chemical effect of CO2 was decoupled.